The Influence of Cash Flow, Net Profit and Company Size on Company Stock Prices in Automotive and Component Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2022 Period - Sakinah, Putri Atika Surya; Sherlita, Erly (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This research aims to determine the influence of cash flow, net profit and company size on stock prices in Automotive and Components Subsector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The factors tested in this research are cash flow, net profit, and company size as independent variables, while stock prices is the dependent variable. The research method used in this research is descriptive and verification methods. The population in this research is the Automotive and Components Subsector companies listed on the Indonesia Stock Exchange for the 2019-2021 period, totaling 12 companies. The sampling technique used was non-probability sampling with a saturated sampling method, so the total sample was 12 companies. The data analysis used is panel data analysis using the Eviews 13 program. The research results show that cash flow, net profit and company size affect stock prices. Apart from that, the research results also show that the influence of cash flow, net profit and company size in contributing to stock prices is 65.3%.